Novel parent-of-origin-specific differentially methylated loci on chromosome 16. - Schulze, Katharina V; Szafranski, Przemyslaw; Lesmana, Harry; Hopkin, Robert J; Hamvas, Aaron; Wambach, Jennifer A; Shinawi, Marwan; Zapata, Gladys; Carvalho, Claudia M B; Liu, Qian; Karolak, Justyna A; Lupski, James R; et al. (Clin Epigenetics, 2019)
BACKGROUND: Congenital malformations associated with maternal uniparental disomy of chromosome 16, upd(16)mat, resemble those observed in newborns with the lethal developmental lung disease, alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV). Interestingly, ACDMPV-causative deletions, involving FOXF1 or its lung-specific upstream enhancer at 16q24.1, arise almost exclusively on the maternally inherited chromosome 16. Given the phenotypic similarities between upd(16)mat and ACDMPV, together with parental allelic bias in ACDMPV, we hypothesized that there may be unknown imprinted loci mapping to chromosome 16 that become functionally unmasked by chromosomal structural variants. RESULTS: To identify parent-of-origin biased DNA methylation, we performed high-resolution bisulfite sequencing of chromosome 16 on peripheral blood and cultured skin fibroblasts from individuals with maternal or paternal upd(16) as well as lung tissue from patients with ACDMPV-causative 16q24.1 deletions and a normal control. We identified 22 differentially methylated regions (DMRs) with ≥ 5 consecutive CpG methylation sites and varying tissue-specificity, including the known DMRs associated with the established imprinted gene ZNF597 and DMRs supporting maternal methylation of PRR25, thought to be paternally expressed in lymphoblastoid cells. Lastly, we found evidence of paternal methylation on 16q24.1 near LINC01082 mapping to the FOXF1 enhancer. CONCLUSIONS: Using high-resolution bisulfite sequencing to evaluate DNA methylation across chromosome 16, we found evidence for novel candidate imprinted loci on chromosome 16 that would not be evident in array-based assays and could contribute to the birth defects observed in patients with upd(16)mat or in ACDMPV.

Bi-allelic POLR3A Loss-of-Function Variants Cause Autosomal-Recessive Wiedemann-Rautenstrauch Syndrome. - Wambach, Jennifer A; Wegner, Daniel J; Patni, Nivedita; Kircher, Martin; Willing, Marcia C; Baldridge, Dustin; Xing, Chao; Agarwal, Anil K; Vergano, Samantha A Schrier; Patel, Chirag; Grange, Dorothy K; Kenney, Amy; et al. (Am J Hum Genet, 2018)
Wiedemann-Rautenstrauch syndrome (WRS), also known as neonatal progeroid syndrome, is a rare disorder of unknown etiology. It has been proposed to be autosomal-recessive and is characterized by variable clinical features, such as intrauterine growth restriction and poor postnatal weight gain, characteristic facial features (triangular appearance to the face, convex nasal profile or pinched nose, and small mouth), widened fontanelles, pseudohydrocephalus, prominent scalp veins, lipodystrophy, and teeth abnormalities. A previous report described a single WRS patient with bi-allelic truncating and splicing variants in POLR3A. Here we present seven additional infants, children, and adults with WRS and bi-allelic truncating and/or splicing variants in POLR3A. POLR3A, the largest subunit of RNA polymerase III, is a DNA-directed RNA polymerase that transcribes many small noncoding RNAs that regulate transcription, RNA processing, and translation. Bi-allelic missense variants in POLR3A have been associated with phenotypes distinct from WRS: hypogonadotropic hypogonadism and hypomyelinating leukodystrophy with or without oligodontia. Our findings confirm the association of bi-allelic POLR3A variants with WRS, expand the clinical phenotype of WRS, and suggest specific POLR3A genotypes associated with WRS and hypomyelinating leukodystrophy.